Synthesis of Nanocomposite Materials for Biodegradable Food Packaging - Johnner Parningotan Sitompul; Daru Setyawan; Aldhita Graffi Nabila; Vita Wonoputri; Hyung Woo Lee (International Journal of Oil Palm, 2019)
This paper concerns on synthesis of nancomposite materials, based on poly(D,Llactic acid)/poly(L-lactic acid). The Poly(L,D-lactic acid) (PDLLA) was produced from L,Dlactic acid through direct polycondensation method and poly(L-lactic acid) (PLLA) derived from L-lactide through ring-opening polymerization method. The PDLLA/PLLA films were produced through solvent casting method. The ratio of PDLLA in the PDLLA/PLLA matrix was determined by adjusting PDLLA fraction. The nanoclay used in this experiment were natural clay (Bentonite) and modified organoclay with quaternary ammonium salt (Cloisite 30B). The PLA blend nanocomposites was produced through solution intercalation with sonication. To determine the effect of amounts of nanoclay and sonication period, these two variable were varied. To analyze chemical structure of PLA, the PLA blend film were tested using Fourier Transform Infrared (FTIR). The dispersion of nanoclay on the PLA blend matrix was analyzed using X-Ray Diffraction (XRD) test. The properties of PLA blend nanocomposites film were then characterized using Universal Testing Machine (UTM), Water Vapor Permeability (WVP) test and the enzymatic biodegradability test. The fraction of PDLLA on the PLA blend was fixed 70 % wt. XRD test showed exfoliation of Cloisite 30B in the PLA matrix while the Bentonite was exfoliated as well as intercalated. The addition of nanoclay improved the tensile strength of PLA blend nanocomposites polymer to the number of 56.26 MPa and 37.65 MPa, respectively. Sonication period of PDLLA/PLLA nanocomposite affected the mechanical properties, barrier properties and polymer biodegradability. Moreover, from the WVP test, the barrier properties of the blend polymers was improved and increased twice compared to that of the pure PDLLA/PLLA.